Efficient identity-based threshold signature scheme from bilinear pairings in standard model. (1st January 2014) - Li, Fei; Gao, Wei; Wang, Guilin; Chen, Kefei; Wang, Xueli
We propose a new identity-based threshold signature (IBTHS) scheme from bilinear pairings enjoying the following advantages in efficiency, security and functionality. The round-complexity of the threshold signing protocol is optimal since each party pays no other communication cost except broadcasting one single message. The computational complexity of the threshold signing procedure is considerably low since there appears no other time-consuming pairing except two pairings for verifying each signature shares. The communication channel requirement of the threshold signing procedure is the lowest since the broadcast channel among signers is enough. It is provably secure with optimal resilience in the standard model. It is the private key associated with an identity rather than a private key of the private key generator (PKG) that is shared among signature generation servers.